2018
DOI: 10.3389/fpsyt.2018.00206
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-Related Dissociation Is Linked With Maladaptive Personality Functioning

Abstract: Background: Extensive research has demonstrated the positive associations among the exposure to traumatic experiences, the levels of dissociation, and the severity of psychiatric symptoms in adults. However, it has been hypothesized in clinical literature that an excessive activation of the dissociative processes following multiple traumatic experiences may jeopardize the psychological and behavioral functioning of the individuals, fostering higher levels of maladaptive personality functioning.Methods: The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…Traumatic experiences, particularly attachment trauma and early relational adverse experiences, not only foster dissociation and psychopathology (Schimmenti, 2017 ) creating a vertical disconnection in the mind-brain-body system but also elicit the impulsivity, lack of effortful control, emotional dysregulation and use of immature defenses that are characteristics of self-other pathologies (see alternative model of personality disorders, DSM-5, 2013), such as BPO or maladaptive personality pathologies in general (Mucci, 2016 , 2018 ; Granieri et al, 2017 , 2018 ).…”
Section: Early Relational Experiences Attachment and The Developmentmentioning
confidence: 99%
“…Traumatic experiences, particularly attachment trauma and early relational adverse experiences, not only foster dissociation and psychopathology (Schimmenti, 2017 ) creating a vertical disconnection in the mind-brain-body system but also elicit the impulsivity, lack of effortful control, emotional dysregulation and use of immature defenses that are characteristics of self-other pathologies (see alternative model of personality disorders, DSM-5, 2013), such as BPO or maladaptive personality pathologies in general (Mucci, 2016 , 2018 ; Granieri et al, 2017 , 2018 ).…”
Section: Early Relational Experiences Attachment and The Developmentmentioning
confidence: 99%
“…On a behavioral level, this adverse influence on brain development is reflected by impaired emotional regulation which was found to mediate the relationship between childhood trauma and adult psychopathology ( 13 , 14 ). Furthermore, recent studies by Schimmenti ( 15 ) and Granieri et al ( 16 ) observed that the link between childhood trauma, adult life psychopathology and personality dysfunction is partially mediated by dissociation. This particular emotional regulation strategy presents a serious obstacle in the functional development of the brain-mind and is considered a primitive defense style related to splitting mechanisms and fragmentation of the self ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the emotional dysregulation resulting from such negative experiences may negatively affect the development of, and interactions among brain structures that are relevant for understanding oneself and one’s own actions, including the hippocampal region involved in the consolidation of memory and the prefrontal cortex involved in executive functioning and decision making, among many other structures damaged by childhood trauma [ 9 ]. Such vulnerability to emotional dysregulation may also become embedded in the individual personality and way of relating with others [ 10 ], thus fostering both severe difficulties in processing and integrating distressing experiences at the mental and bodily level, and severe distrust of others for receiving protective closeness and interpersonal regulation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%